THE IMPORTANCE OF WATERWAYS IN TRADE AND ECONOMIC RELATIONS BETWEEN THE STATES OF UZBEKISTAN AND AFGHANISTAN - Dusmatova Oltinoy Tursun kizi (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article, in the works of tourists, ambassadors, diplomatic officials, researchers of the 2nd half of the 19th-early 20th centuries, information on the issue of the establishment of trade and economic relations between the emirate of Bukhara and Afghanistan was studied and analyzed in detail.